The Effect of Foreign Direct Investment and External Debt on Economic Growth in Indonesia - Vido Metti Sitepu (International Journal on Social Science, Economics and Art, 2021)
Indonesia as a development country, has a good economic growth in the 1990's. It shows by increasing of GDP year by year, stabilization of inflation, etc. But since 1997's economic crisis in Asia's countries, Indonesia's economic growth has been declining. It effected the monetary sector and real sector, and add again with progressively the amount of foreign debt of Indonesia, so that effect of Rupiah rate wich progressively weakening. This paper will analyze the foreign direct investment also foreign debt, on the economic growth of Indonesia. By using the OLS model on Indonesia yearly data from 1975-2009 and the confirm the significant of these independent variables as the factors that effected the economic growth of Indonesia. Foreign direct investment and foreing debt represent the way able to be gone through by government in overcoming deficit of national saving utilize to push the national development to get the good economic growth. Pursuant to things told above, writer try to study the problem of economic growth in Indonesia in its relation with the foreign direct investment and foreign debt by lifting title “Influence on The Foreign Direct Investment and The Foreign Debt to Economic Growth of Indonesia”.